Diet-induced vitamin D deficiency reduces skeletal muscle mitochondrial respiration. Issue 2 (May 2021) - Ashcroft, Stephen P; Fletcher, Gareth; Philp, Ashleigh M; Jenkinson, Carl; Das, Shatarupa; Hansbro, Philip M; Atherton, Philip J; Philp, Andrew
Abstract : Vitamin D deficiency is associated with symptoms of skeletal muscle myopathy including muscle weakness and fatigue. Recently, vitamin D-related metabolites have been linked to the maintenance of mitochondrial function within skeletal muscle. However, current evidence is limited to in vitro models and the effects of diet-induced vitamin D deficiency upon skeletal muscle mitochondrial function in vivo have received little attention. In order to examine the role of vitamin D in the maintenance of mitochondrial function in vivo, we utilised an established model of diet-induced vitamin D deficiency in C57BL/6J mice. Mice were either fed a control diet (2200 IU/kg i.e. vitamin D replete) or a vitamin D-deplete (0 IU/kg) diet for periods of 1, 2 and 3 months. Gastrocnemius muscle mitochondrial function and ADP sensitivity were assessed via high-resolution respirometry and mitochondrial protein content via immunoblotting. As a result of 3 months of diet-induced vitamin D deficiency, respiration supported via complex I + II (CI + IIP ) and the electron transport chain (ETC) were 35 and 37% lower when compared to vitamin D-replete mice ( P < 0.05). Despite functional alterations, citrate synthase activity, AMPK phosphorylation, mitofilin, OPA1 and ETC subunit protein content remained unchanged in response to dietary intervention ( P > 0.05). In conclusion, we report that 3 months of diet-induced vitamin D deficiency reduced skeletal muscle mitochondrial respiration in C57BL/6J mice. Our data, when combined with previous in vitro observations, suggest that vitamin D-mediated regulation of mitochondrial function may underlie the exacerbated muscle fatigue and performance deficits observed during vitamin D deficiency.